Option 3 : [tex]f(3)=-101[/tex] is the correct answer.
Explanation:
It is given that the recursive equation is [tex]f(n+1)=-3f(n)+1[/tex] and also [tex]$f(0)=4$[/tex]
To determine the value of [tex]f(3)[/tex], we need to know the previous terms.
Thus, let us substitute [tex]n=0,1,2[/tex] in the equation [tex]f(n+1)=-3f(n)+1[/tex]
For [tex]n=0[/tex], we get,
[tex]$\begin{aligned} f(0+1) &=-3 f(0)+1 \\ f(1) &=-3(4)+1 \\ f(1) &=-12+1 \\ f(1) &=-11 \end{aligned}$[/tex]
For [tex]n=1[/tex], we get,
[tex]$\begin{aligned} f(1+1) &=-3(-11)+1 \\ f(2) &=33+1 \\ f(2) &=34\end{aligned}$[/tex]
For [tex]n=2[/tex], we get,
[tex]$\begin{aligned} f(2+1) &=-3(34)+1 \\ f(3) &=-102+1 \\ f(3) &=-101 \end{aligned}$[/tex]
Thus, the value of [tex]f(3)[/tex] is -101.
Hence, Option 3 is the correct answer.